2022
DOI: 10.24191/ji.v17i1.15937
|View full text |Cite
|
Sign up to set email alerts
|

Financial Statement Fraud: Evidence from Malaysian Public Listed Companies

Abstract: Financial statement fraud is seen as a rampant problem around the world. Early detection is one of the ways to curb financial statement fraud, and it has motivated this study to be conducted.  The main objective of this study is to investigate the primary factors that influence the public listed companies in Malaysia to be involved in financial statement fraud. The sample used in this study comprised 40 financial statement fraud companies matched with another 40 non-financial statement fraud companies listed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The fraud issue has gained the attention of many parties including regulators, policymakers, and top management of large companies (Salin and Ismail, 2015). In fact, the corporate governance practices and policies were strengthened through the execution of the Malaysian Code of Corporate Governance (MCCG) in 2000 by the Securities Commission Malaysia (SC), which became a significant tool for governance reform (Securities Commission, 2017).…”
Section: Ethical Issues Practices and Communicationmentioning
confidence: 99%
“…The fraud issue has gained the attention of many parties including regulators, policymakers, and top management of large companies (Salin and Ismail, 2015). In fact, the corporate governance practices and policies were strengthened through the execution of the Malaysian Code of Corporate Governance (MCCG) in 2000 by the Securities Commission Malaysia (SC), which became a significant tool for governance reform (Securities Commission, 2017).…”
Section: Ethical Issues Practices and Communicationmentioning
confidence: 99%
“…In this study, the focus is on fraud that occurs in financial reporting. Financial reporting fraud had escalated, and it was found that 77% of the financial reporting fraud is committed by individuals in the company's senior management, executives, and accounting officers through sales and buy operations or during the consolidation of company accounts (Norziaton, 2022). Moreover, a company manipulates financial reporting because it wants to show that its performance looks better than the actual outcome and ensure that they maintain a favourable position in the future.…”
Section: Background Of Studymentioning
confidence: 99%
“…A manipulated financial statement will lead the user to choose the incorrect investment decisions. The complexity of financial statement fraud has taken tremendous interest over the distance past, and the concern will remain to many parties because it plays a significant role in analyzing the company's performance (Ismail Khan, et al, 2022). Financial statements fraud involves falsification of an organization's financial statements such as the creation of fictitious revenue, understated liabilities, and improper asset valuation (KPMG Malaysia, 2014, ACFE, 2019).…”
Section: Introductionmentioning
confidence: 99%